An intravital microscopy-based approach to assess intestinal permeability and epithelial cell shedding performance - Martínez Sánchez, Luz del Carmen; Pradhan, Rashmita; Ngo, Phuong A.; Erkert, Lena; Becker, Lea; Watson, Alastair J.; Atreya, Imke; Neurath, Markus; Lopez Posadas, Rocío (Journal of Visualized Experiments, 2020)
Intravital microscopy of the gut using confocal imaging allows real time observation of epithelial cell shedding and barrier leakage in living animals. Therefore, the intestinal mucosa of anesthetized mice is topically stained with unspecific staining (acriflavine) and a fluorescent tracer (rhodamine-B dextran), mounted on a saline solution-rinsed plate and directly imaged using a confocal microscope. This technique can complement other non-invasive techniques to identify leakage of intestinal permeability, such as transmucosal passage of orally administered tracers. Besides this, the approach presented here allows the direct observation of cell shedding events at real-time. In combination with appropriate fluorescent reporter mice, this approach is suitable for shedding light into cellular and molecular mechanisms controlling intestinal epithelial cell extrusion, as well as to other biological processes. In the last decades, interesting studies using intravital microscopy have contributed to knowledge on endothelial permeability, immune cell gut homing, immune-epithelial communication and invasion of luminal components, among others. Together, the protocol presented here would not only help increase the understanding of mechanisms controlling epithelial cell extrusion, but could also be the basis for the developmental of other approaches to be used as instruments to visualize other highly dynamic cellular process, even in other tissues. Among technical limitations, optical properties of the specific tissue, as well as the selected imaging technology and microscope configuration, would in turn, determine the imaging working distance, and resolution of acquired images.
CRIS-Team Scopus Importer:2020-12-25

ATP citrate lyase (ACLY)-dependent immunometabolism in mucosal T cells drives experimental colitis in vivo - Schulz-Kuhnt, Anja; Rühle, Katharina; Javidmehr, Asal; Döbrönti, Michael; Biwank, Jana; Knittel, Selina; Neidlinger, Peter; Leupold, Jannik; Liu, Lijuan; Dedden, Mark; Taudte, Regina Verena; Geßner, Arne; et al. (Gut, 2024)
Objective Mucosal T cells play a major role in inflammatory bowel disease (IBD). However, their immunometabolism during intestinal inflammation is poorly understood. Due to its impact on cellular metabolism and proinflammatory immune cell function, we here focus on the enzyme ATP citrate lyase (ACLY) in mucosal T cell immunometabolism and its relevance for IBD. Design ACLY expression and its immunometabolic impact on colitogenic T cell function were analysed in mucosal T cells from patients with IBD and in two experimental colitis models. Results ACLY was markedly expressed in colon tissue under steady-state conditions but was significantly downregulated in lamina propria mononuclear cells in experimental dextran sodium sulfate-induced colitis and in CD4+ and to a lesser extent in CD8+ T cells infiltrating the inflamed gut in patients with IBD. ACLY-deficient CD4+ T cells showed an impaired capacity to induce intestinal inflammation in a transfer colitis model as compared with wild-type T cells. Assessment of T cell immunometabolism revealed that ACLY deficiency dampened the production of IBD-relevant cytokines and impaired glycolytic ATP production but enriched metabolites involved in the biosynthesis of phospholipids and phosphatidylcholine. Interestingly, the short-chain fatty acid butyrate was identified as a potent suppressor of ACLY expression in T cells, while IL-36α and resolvin E1 induced ACLY levels. In a translational approach, in vivo administration of the butyrate prodrug tributyrin downregulated mucosal infiltration of ACLYhigh CD4+ T cells and ameliorated chronic colitis. Conclusion ACLY controls mucosal T cell immunometabolism and experimental colitis. Therapeutic modulation of ACLY expression in T cells emerges as a novel strategy to promote the resolution of intestinal inflammatio

Blockade of αEβ7 integrin suppresses accumulation of CD8+ and Th9 lymphocytes from patients with IBD in the inflamed gut in vivo - Zundler, Sebastian; Schillinger, Daniela; Fischer, Anika; Atreya, Raja; Lopez Posadas, Rocío; Watson, Alastair; Neufert, Clemens; Atreya, Imke; Neurath, Markus (Gut, 2016)
Objective Therapeutically targeting lymphocyte adhesion is of increasing relevance in IBD. Yet, central aspects of the action of antiadhesion compounds are incompletely understood. We investigated the role of αEβ7 and α4β7 integrins and their blockade by vedolizumab and etrolizumab for trafficking of IBD T lymphocytes in an in vivo model of homing to and retention in the inflamed gut. Design We explored integrin expression in patients with IBD by flow cytometry and immunohistochemistry, while regulation of integrins was studied in T cell cultures. The functional relevance of integrins was assessed by adhesion assays and a recently established humanised mouse model in dextran sodium sulfate-treated immunodeficient mice. Results High expression of αEβ7 was noted on CD8+ and CD4+ Th9 cells, while α4β7 was expressed on CD8+, Th2 and Th17 cells. T cell receptor stimulation and transforming growth factor β were key inducers of αEβ7 on human T cells, while butyric acid suppressed αEβ7. In comparison to α4β7 blockade via vedolizumab, blockade of β7 via etrolizumab surrogate antibody superiorly reduced colonic numbers of CD8+ and Th9 cells in vivo after 3 hours, while no difference was noted after 0.5 hours. AEβ7 expression was higher on CD8+ T cells from patients with IBD under vedolizumab therapy. Conclusions AEβ7 is of key relevance for gut trafficking of IBD CD8+ T cells and CD4+ Th9 cells in vivo and mainly retention might account for this effect. These findings indicate that blockade of αEβ7 in addition to α4β7 may be particularly effective in intestinal disorders with expansion of CD8+ and Th9 cells such as IBD.
EVALuna2:2222

Designer Thiopurine-analogues for Optimised Immunosuppression in Inflammatory Bowel Diseases - Atreya, Imke; Diall, Alexandra; Dvorsky, Radovan; Atreya, Raja; Henninger, Christian; Gruen, Mathias; Hofmann, Ute; Schaeffeler, Elke; Lopez Posadas, Rocío; Daehn, Ilse; Zenker, Stefanie; Doebroenti, Michael; et al. (Journal of Crohns & Colitis, 2016)
The clinical use of azathioprine and 6-mercaptopurine is limited by their delayed onset of action and potential side effects such as myelosuppression and hepatotoxicity. As these drugs specifically target the Vav1/Rac1 signalling pathway in T lamina propria lymphocytes via their metabolite 6-thio-GTP, we studied expression and optimised suppression of this pathway in inflammatory bowel diseases [IBD].Rac1 and Vav1 expressions were analysed in mucosal immune cells in IBD patients. Targeted molecular modelling of the 6-thio-GTP molecule was performed to optimise Rac1 blockade; 44 modified designer thiopurine-analogues were tested for apoptosis induction, potential toxicity, and immunosuppression. Activation of the Vav1/Rac1 pathway in lymphocytes was studied in IBD patients and in lamina propria immune cells in the presence or absence of thiopurine-analogues.Several thiopurine-analogues induced significantly higher T cell apoptosis than 6-mercaptopurine. We identified a compound, denoted B-0N, based on its capacity to mediate earlier and stronger induction of T cell apoptosis than 6-mercaptopurine. B-0N-treatment resulted in accelerated inhibition of Rac1 activity in primary peripheral blood T cells as well as in intestinal lamina propria immune cells. Compared with 6-thio-GTP and 6-mercaptopurine, B-0N-treatment was associated with decreased myelo- and hepatotoxicity.The Vav1/Rac1 pathway is activated in mucosal immune cells in IBD. The designer thiopurine-analogue B-0N induces immunosuppression more potently than 6-mercaptopurine.
EVALuna2:2190

Differential effects of ?4?7 and GPR15 on homing of effector and regulatory T cells from patients with UC to the inflamed gut in vivo - Fischer, Anika; Zundler, Sebastian; Atreya, Raja; Rath, Timo; Voskens, Caroline; Hirschmann, Simon; Lopez Posadas, Rocío; Watson, Alastair; Becker, Christoph; Schuler, Gerold; Neufert, Clemens; Atreya, Imke; et al. (Gut, 2016)
Gut homing of lymphocytes via adhesion molecules has recently emerged as new target for therapy in IBDs. We aimed to analyse the in vivo homing of effector (Teff) and regulatory (Treg) T cells to the inflamed gut via ?4?7 and G protein receptor GPR15.We assessed the expression of homing receptors on T cells in peripheral blood and inflamed mucosa. We studied the migration pattern and homing of Teff and Treg cells to the inflamed gut using intravital confocal microscopy and FACS in a humanised mouse model in dextran sodium sulfate-treated NSG (NOD.Cg-Prkdcscid-Il2rgtm1Wjl/SzJ) mice.Expression of GPR15 and ?4?7 was significantly increased on Treg rather than Teff cells in peripheral blood of patients with UC as compared with Crohn's disease and controls. In vivo analysis in a humanised mouse model showed augmented gut homing of UC Treg cells as compared with controls. Moreover, suppression of UC (but not control) Teff and Treg cell homing was noted upon treatment with the ?4?7 antibody vedolizumab. In contrast, siRNA blockade of GPR15 had only effects on homing of Teff cells but did not affect Treg homing in UC. Clinical vedolizumab treatment was associated with marked expansion of UC Treg cells in peripheral blood.?4?7 rather than GPR15 is crucial for increased colonic homing of UC Treg cells in vivo, while both receptors control UC Teff cell homing. Vedolizumab treatment impairs homing of UC Treg cells leading to their accumulation in peripheral blood with subsequent suppression of systemic Teff cell expansion.
EVALuna2:2173

Dynamic traction force measurements of migrating immune cells in 3D biopolymer matrices - Böhringer, David; Cóndor, Mar; Bischof, Lars; Czerwinski, Tina; Gampl, Niklas; Ngo, Phuong; Bauer, Andreas; Bosch-Voskens, Caroline; Lopez Posadas, Rocío; Franze, Kristian; Budday, Silvia; Mark, Christoph; et al. (Nature Physics, 2024)
Immune cells, such as natural killer cells, migrate with high speeds of several micrometres per minute through dense tissue. However, the magnitude of the traction forces during this migration is unknown. Here we present a method to measure dynamic traction forces of fast migrating cells in biopolymer matrices from the observed matrix deformations. Our method accounts for the mechanical nonlinearity of the three-dimensional tissue matrix and can be applied to time series of confocal or bright-field image stacks. It allows for precise force reconstruction over a wide range of force magnitudes and object sizes—even when the imaged volume captures only a small part of the matrix deformation field. We demonstrate the broad applicability of our method by measuring forces from around 1 nN for axon growth cones up to around 10 μN for mouse intestinal organoids. We find that natural killer cells show bursts of large traction forces around 50 nN that increase with matrix stiffness. These force bursts are driven by myosin II contractility, mediated by integrin β1 adhesions, focal adhesion kinase and Rho-kinase activity, and occur predominantly when the cells migrate through narrow matrix pores.
CRIS-Team Scopus Importer:2024-11-29

Engineering Therapeutic Regulatory T Cells to Overexpress G Protein-Coupled Receptor 15 Improves Functional Fitness for In Vivo Gut Homing - Müller, Tanja; Liu, Lijuan; Wiesinger, Manuel; Atreya, Imke; Atreya, Raja; Bacher, Petra; Becker, Christoph; Bojarski, Christian; Britzen-Laurent, Nathalie; Bosch-Voskens, Caroline; Chang, Hyun Dong; Diefenbach, Andreas; et al. (Gastroenterology, 2025)
CRIS-Team Scopus Importer:2025-01-31

Epithelial RAC1-dependent cytoskeleton dynamics controls cell mechanics, cell shedding and barrier integrity in intestinal inflammation - Martínez Sánchez, Luz del Carmen; Phuong Anh Ngo; Pradhan, Rashmita; Becker, Lukas S; Böhringer, David; Soteriou, Despina; Kubankova, Marketa; Schweitzer, Christine; Koch, Tatyana; Thonn, Veronika; Erkert, Lena; Stolzer, Iris; et al. (Gut, 2022)
Objective Increased apoptotic shedding has been linked to intestinal barrier dysfunction and development of inflammatory bowel diseases (IBD). In contrast, physiological cell shedding allows the renewal of the epithelial monolayer without compromising the barrier function. Here, we investigated the role of live cell extrusion in epithelial barrier alterations in IBD. Design Taking advantage of conditional GGTase and RAC1 knockout mice in intestinal epithelial cells (Pggt1b (i Delta IEC) and Rac1 (i Delta IEC) mice), intravital microscopy, immunostaining, mechanobiology, organoid techniques and RNA sequencing, we analysed cell shedding alterations within the intestinal epithelium. Moreover, we examined human gut tissue and intestinal organoids from patients with IBD for cell shedding alterations and RAC1 function. Results Epithelial Pggt1b deletion led to cytoskeleton rearrangement and tight junction redistribution, causing cell overcrowding due to arresting of cell shedding that finally resulted in epithelial leakage and spontaneous mucosal inflammation in the small and to a lesser extent in the large intestine. Both in vivo and in vitro studies (knockout mice, organoids) identified RAC1 as a GGTase target critically involved in prenylation-dependent cytoskeleton dynamics, cell mechanics and epithelial cell shedding. Moreover, inflamed areas of gut tissue from patients with IBD exhibited funnel-like structures, signs of arrested cell shedding and impaired RAC1 function. RAC1 inhibition in human intestinal organoids caused actin alterations compatible with arresting of cell shedding. Conclusion Impaired epithelial RAC1 function causes cell overcrowding and epithelial leakage thus inducing chronic intestinal inflammation. Epithelial RAC1 emerges as key regulator of cytoskeletal dynamics, cell mechanics and intestinal cell shedding. Modulation of RAC1 might be exploited for restoration of epithelial integrity in the gut of patients with IBD.
CRIS-Team WoS Importer:2022-03-25

Hobit- and Blimp-1-driven CD4(+) tissue-resident memory T cells control chronic intestinal inflammation - Zundler, Sebastian; Becker, Emily; Spocinska, Marta; Slawik, Monique; Parga-Vidal, Loreto; Stark, Regina; Wiendl, Maximilian; Atreya, Raja; Rath, Timo; Leppkes, Moritz; Hildner, Kai; Lopez Posadas, Rocío; et al. (Nature Immunology, 2019)
Although tissue-resident memory T cells (T-RM cells) have been shown to regulate host protection in infectious disorders, their function in inflammatory bowel disease (IBD) remains to be investigated. Here we characterized T-RM cells in human IBD and in experimental models of intestinal inflammation. Pro-inflammatory T-RM cells accumulated in the mucosa of patients with IBD, and the presence of CD4(+)CD69(+)CD103(+) T-RM cells was predictive of the development of flares. In vivo, functional impairment of T-RM cells in mice with double knockout of the T-RM-cell-associated transcription factors Hobit and Blimp-1 attenuated disease in several models of colitis, due to impaired cross-talk between the adaptive and innate immune system. Finally, depletion of T-RM cells led to a suppression of colitis activity. Together, our data demonstrate a central role for T-RM cells in the pathogenesis of chronic intestinal inflammation and suggest that these cells could be targets for future therapeutic approaches in IBD.
CRIS-Team WoS Importer:2019-03-06

IL-3 receptor signalling suppresses chronic intestinal inflammation by controlling mechanobiology and tissue egress of regulatory T cells. - Ullrich, Karen; Derdau, Julia; Baltes, Carsten; Battistella, Alice; Rosso, Gonzalo; Uderhardt, Stefan; Schulze, Lisa; Liu, Lijuan; Dedden, Mark; Spocinska, Marta; Kainka, Lucina; Kubánková, Markéta; et al. (Gut, 2023)
IL-3 has been reported to be involved in various inflammatory disorders, but its role in inflammatory bowel disease (IBD) has not been addressed so far. Here, we determined IL-3 expression in samples from patients with IBD and studied the impact of Il3 or Il3r deficiency on T cell-dependent experimental colitis. We explored the mechanical, cytoskeletal and migratory properties of Il3r -/- and Il3r +/+ T cells using real-time deformability cytometry, atomic force microscopy, scanning electron microscopy, fluorescence recovery after photobleaching and in vitro and in vivo cell trafficking assays. We observed that, in patients with IBD, the levels of IL-3 in the inflamed mucosa were increased. In vivo, experimental chronic colitis on T cell transfer was exacerbated in the absence of Il-3 or Il-3r signalling. This was attributable to Il-3r signalling-induced changes in kinase phosphorylation and actin cytoskeleton structure, resulting in increased mechanical deformability and enhanced egress of Tregs from the inflamed colon mucosa. Similarly, IL-3 controlled mechanobiology in human Tregs and was associated with increased mucosal Treg abundance in patients with IBD. Collectively, our data reveal that IL-3 signaling exerts an important regulatory role at the interface of biophysical and migratory T cell features in intestinal inflammation and suggest that this might be an interesting target for future intervention.
EVALuna2:539503

ILC2 Lung-Homing in Cystic Fibrosis Patients: Functional Involvement of CCR6 and Impact on Respiratory Failure - Schulz-Kuhnt, Anja; Greif, Vicky; Hildner, Kai; Knipfer, Lisa; Döbrönti, Michael; Zirlik, Sabine; Fuchs, Florian; Atreya, Raja; Zundler, Sebastian; Lopez Posadas, Rocío; Neufert, Clemens; Ramming, Andreas; et al. (Frontiers in Immunology, 2020)
Cystic fibrosis patients suffer from a progressive, often fatal lung disease, which is based on a complex interplay between chronic infections, locally accumulating immune cells and pulmonary tissue remodeling. Although group-2 innate lymphoid cells (ILC2s) act as crucial initiators of lung inflammation, our understanding of their involvement in the pathogenesis of cystic fibrosis remains incomplete. Here we report a marked decrease of circulating CCR6+ ILC2s in the blood of cystic fibrosis patients, which significantly correlated with high disease severity and advanced pulmonary failure, strongly implicating increased ILC2 homing from the peripheral blood to the chronically inflamed lung tissue in cystic fibrosis patients. On a functional level, the CCR6 ligand CCL20 was identified as potent promoter of lung-directed ILC2 migration upon inflammatory conditions in vitro and in vivo using a new humanized mouse model with light-sheet fluorescence microscopic visualization of lung-accumulated human ILC2s. In the lung, blood-derived human ILC2s were able to augment local eosinophil and neutrophil accumulation and induced a marked upregulation of pulmonary type-VI collagen expression. Studies in primary human lung fibroblasts additionally revealed ILC2-derived IL-4 and IL-13 as important mediators of this type-VI collagen-inducing effect. Taken together, the here acquired results suggest that pathologically increased CCL20 levels in cystic fibrosis airways induce CCR6-mediated lung homing of circulating human ILC2s. Subsequent ILC2 activation then triggers local production of type-VI collagen and might thereby drive extracellular matrix remodeling potentially influencing pulmonary tissue destruction in cystic fibrosis patients. Thus, modulating the lung homing capacity of circulating ILC2s and their local effector functions opens new therapeutic avenues for cystic fibrosis treatment.
CRIS-Team Scopus Importer:2020-06-02
Keywords: CCR6; cystic fibrosis; group-2 innate lymphoid cells; tissue remodeling; type-VI collagen

Impact of Epithelial Cell Shedding on Intestinal Homeostasis - Ngo, Phuong A.; Neurath, Markus; Lopez Posadas, Rocío (International Journal of Molecular Sciences, 2022)
The gut barrier acts as a first line of defense in the body, and plays a vital role in nutrition and immunoregulation. A layer of epithelial cells bound together via intercellular junction proteins maintains intestinal barrier integrity. Based on a tight equilibrium between cell extrusion and cell restitution, the renewal of the epithelium (epithelial turnover) permits the preservation of cell numbers. As the last step within the epithelial turnover, cell shedding occurs due to the pressure of cell division and migration from the base of the crypt. During this process, redistribution of tight junction proteins enables the sealing of the epithelial gap left by the extruded cell, and thereby maintains barrier function. Disturbance in cell shedding can create transient gaps (leaky gut) or cell accumulation in the epithelial layer. In fact, numerous studies have described the association between dysregulated cell shedding and infection, inflammation, and cancer; thus epithelial cell extrusion is considered a key defense mechanism. In the gastrointestinal tract, altered cell shedding has been observed in mouse models of intestinal inflammation and appears as a potential cause of barrier loss in human inflammatory bowel disease (IBD). Despite the relevance of this process, there are many unanswered questions regarding cell shedding. The investigation of those mechanisms controlling cell extrusion in the gut will definitely contribute to our understanding of intestinal homeostasis. In this review, we summarized the current knowledge about intestinal cell shedding under both physiological and pathological circumstances.
CRIS-Team Scopus Importer:2022-04-29
Keywords: cell extrusion; colorectal cancer; epithelial cell shedding; inflammatory bowel disease (IBD); leaky gut

Inhibiting PGGT1B Disrupts Function of RHOA, Resulting in T-cell Expression of Integrin α4β7 and Development of Colitis in Mice - Lopez Posadas, Rocío; Fastancz, Petra; Martínez-Sánchez, Luz del Carmen; Panteleev-Ivlev, Julia; Thonn, Veronika; Kisseleva, Tatyana; Becker, Lukas S.; Schulz-Kuhnt, Anja; Zundler, Sebastian; Wirtz, Stefan; Atreya, Raja; Carlé, Birgitta-Elisabeth; et al. (Gastroenterology, 2019)
Background & Aims: It is not clear how regulation of T-cell function is altered during development of inflammatory bowel diseases (IBD). We studied the mechanisms by which geranylgeranyltransferase-mediated prenylation controls T-cell localization to the intestine and chronic inflammation. Methods: We generated mice with T-cell–specific disruption of the geranylgeranyltransferase type I, beta subunit gene (Pggt1b), called Pggt1bΔCD4 mice, or the ras homolog family member A gene (Rhoa), called RhoaΔCD4 mice. We also studied mice with knockout of CDC42 or RAC1 and wild-type mice (controls). Intestinal tissues were analyzed by histology, multiphoton and confocal microscopy, and real-time polymerase chain reaction. Activation of CDC42, RAC1, and RHOA were measured with G-LISA, cell fractionation, and immunoblots. T cells and lamina propria mononuclear cells from mice were analyzed by flow cytometry or transferred to Rag1–/– mice. Mice were given injections of antibodies against integrin alpha4beta7 or gavaged with the RORC antagonist GSK805. We obtained peripheral blood and intestinal tissue samples from patients with and without IBD and analyzed them by flow cytometry. Results: Pggt1bΔCD4 mice developed spontaneous colitis, characterized by thickening of the intestinal wall, edema, fibrosis, accumulation of T cells in the colon, and increased expression of inflammatory cytokines. Compared with control CD4+ T cells, PGGT1B-deficient CD4+ T cells expressed significantly higher levels of integrin alpha4beta7, which regulates their localization to the intestine. Inflammation induced by transfer of PGGT1B-deficient CD4+ T cells to Rag1–/– mice was blocked by injection of an antibody against integrin alpha4beta7. Lamina propria of Pggt1bΔCD4 mice had increased numbers of CD4+ T cells that expressed RORC and higher levels of cytokines produced by T-helper 17 cells (granulocyte-macrophage colony-stimulating factor, interleukin [IL]17A, IL17F, IL22, and tumor necrosis factor [TNF]). The RORC inverse agonist GSK805, but not antibodies against IL17A or IL17F, prevented colitis in Pggt1bΔCD4 mice. PGGT1B-deficient CD4+ T cells had decreased activation of RHOA. RhoAΔCD4 mice had a similar phenotype to Pggt1bΔCD4 mice, including development of colitis, increased numbers of CD4+ T cells in colon, increased expression of integrin alpha4beta7 by CD4+ T cells, and increased levels of IL17A and other inflammatory cytokines in lamina propria. T cells isolated from intestinal tissues from patients with IBD had significantly lower levels of PGGT1B than tissues from individuals without IBD. Conclusion: Loss of PGGT1B from T cells in mice impairs RHOA function, increasing CD4+ T-cell expression of integrin alpha4beta7 and localization to colon, resulting in increased expression of inflammatory cytokines and colitis. T cells isolated from gut tissues from patients with IBD have lower levels of PGGT1B than tissues from patients without IBD.
CRIS-Team Scopus Importer:2019-10-08
Keywords: IBD; Immune Regulation; Mouse Models; Prenylation

Interplay of GTPases and Cytoskeleton in Cellular Barrier Defects during Gut Inflammation - Lopez Posadas, Rocío; Stürzl, Michael; Atreya, Imke; Neurath, Markus; Britzen-Laurent, Nathalie (Frontiers in Immunology, 2017)
An essential role of the intestine is to build and maintain a barrier preventing the luminal gut microbiota from invading the host. This involves two coordinated physical and immunological barriers formed by single layers of intestinal epithelial and endothelial cells, which avoid the activation of local immune responses or the systemic dissemination of microbial agents, and preserve tissue homeostasis. Accordingly, alterations of epithelial and endothelial barrier functions have been associated with gut inflammation, for example during inflammatory bowel disease (IBD). The discriminative control of nutriment uptake and sealing toward potentially pathological microorganisms requires a profound regulation of para- and transcellular permeability. On the subcellular level, the cytoskeleton exerts key regulatory functions in the maintenance of cellular barriers. Increased epithelial/endothelial permeability occurs primarily as a result of a reorganization of cytoskeletal-junctional complexes. Pro-inflammatory mediators such as cytokines can induce cytoskeletal rearrangements, causing inflammation-dependent defects in gut barrier function. In this context, small GTPases of the Rho family and large GTPases from the Dynamin superfamily appear as major cellular switches regulating the interaction between intercellular junctions and actomyosin complexes, and in turn cytoskeleton plasticity. Strikingly, some of these proteins, such as RhoA or guanylate-binding protein-1 (GBP-1) have been associated with gut inflammation and IBD. In this review, we will summarize the role of small and large GTPases for cytoskeleton plasticity and epithelial/endothelial barrier in the context of gut inflammation.
EVALuna2:15286

Matricellular Protein SPARCL1 Regulates Blood Vessel Integrity and Antagonizes Inflammatory Bowel Disease - Regensburger, Daniela; Tenkerian, Clara; Pürzer, Victoria; Schmid, Benjamin; Wohlfahrt, Thomas; Stolzer, Iris; Lopez Posadas, Rocío; Günther, Claudia; Waldner, Maximilian; Becker, Christoph; Sticht, Heinrich; Petter, Katja; et al. (Inflammatory Bowel Diseases, 2021)
Background The understanding of vascular plasticity is key to defining the role of blood vessels in physiologic and pathogenic processes. In the present study, the impact of the vascular quiescence marker SPARCL1 on angiogenesis, capillary morphogenesis, and vessel integrity was evaluated. Methods Angiogenesis was studied using the metatarsal test, an ex vivo model of sprouting angiogenesis. In addition, acute and chronic dextran sodium sulfate colitis models with SPARCL1 knockout mice were applied. Results This approach indicated that SPARCL1 inhibits angiogenesis and supports vessel morphogenesis and integrity. Evidence was provided that SPARCL1-mediated stabilization of vessel integrity counteracts vessel permeability and inflammation in acute and chronic dextran sodium sulfate colitis models. Structure-function analyses of purified SPARCL1 identified the acidic domain of the protein necessary for its anti-angiogenic activity. Conclusions Our findings inaugurate SPARCL1 as a blood vessel–derived anti-angiogenic molecule required for vessel morphogenesis and integrity. SPARCL1 opens new perspectives as a vascular marker of susceptibility to colitis and as a therapeutic molecule to support blood vessel stability in this disease. <br
Keywords: angiogenesis; blood vessel; DSS colitis; endothelial cell; inflammatory bowel disease; permeability; SPARCL1

Molecular pathways driving disease-specific alterations of intestinal epithelial cells - Lopez Posadas, Rocío; Neurath, Markus; Atreya, Imke (Cellular and Molecular Life Sciences, 2017)
Due to the fact that chronic inflammation as well as tumorigenesis in the gut is crucially impacted by the fate of intestinal epithelial cells, our article provides a comprehensive overview of the composition, function, regulation and homeostasis of the gut epithelium. In particular, we focus on those aspects which were found to be altered in the context of inflammatory bowel diseases or colorectal cancer and also discuss potential molecular targets for a disease-specific therapeutic intervention.
EVALuna2:33826

Rapid single-cell physical phenotyping of mechanically dissociated tissue biopsies - Soteriou, Despina; Kubankova, Marketa; Schweitzer, Christine; Lopez Posadas, Rocío; Pradhan, Rashmita; Thoma, Oana-Maria; Györfi, Andrea-Hermina; Matei, Alexandru-Emil; Waldner, Maximilian; Distler, Jörg; Scheuermann, Stefan; Langejuergen, Jens; et al. (Nature Biomedical Engineering, 2023)
A method for the sequential assessment of the physical phenotypes of suspended cells singularized from tissue biopsies by mechanical dissociation allows for rapid diagnoses.
CRIS-Team WoS Importer:2023-05-05

Rho GTPases as Key Molecular Players within Intestinal Mucosa and GI Diseases - Pradhan, Rashmita; Ngo, Phuong A.; Martínez Sánchez, Luz del Carmen; Neurath, Markus; Lopez Posadas, Rocío (Cells, 2021)
Rho proteins operate as key regulators of the cytoskeleton, cell morphology and trafficking. Acting as molecular switches, the function of Rho GTPases is determined by guanosine triphosphate (GTP)/guanosine diphosphate (GDP) exchange and their lipidation via prenylation, allowing their binding to cellular membranes and the interaction with downstream effector proteins in close proximity to the membrane. A plethora of in vitro studies demonstrate the indispensable function of Rho proteins for cytoskeleton dynamics within different cell types. However, only in the last decades we have got access to genetically modified mouse models to decipher the intricate regulation between members of the Rho family within specific cell types in the complex in vivo situation. Translationally, alterations of the expression and/or function of Rho GTPases have been associated with several pathological conditions, such as inflammation and cancer. In the context of the GI tract, the continuous crosstalk between the host and the intestinal microbiota requires a tight regulation of the complex interaction between cellular components within the intestinal tissue. Recent studies demonstrate that Rho GTPases play important roles for the maintenance of tissue homeostasis in the gut. We will summarize the current knowledge on Rho protein function within individual cell types in the intestinal mucosa in vivo, with special focus on intestinal epithelial cells and T cells.
CRIS-Team WoS Importer:2021-02-05

Spatial Single Cell Profiling Using Imaging Mass Cytometry: Inflammatory Versus Penetrating Crohn's Disease - Lehmann, Malte; Weixler, Benjamin; Elezkurtaj, Sefer; Loddenkemper, Christopher; Atreya, Imke; Atreya, Raja; Bacher, Petra; Becker, Christoph; Bojarski, Christian; Britzen-Laurent, Nathalie; Bosch-Voskens, Caroline; Chang, Hyun Dong; et al. (Journal of Crohns & Colitis, 2024)
Background and Aims: Fistula formation is a major complication in Crohn's disease [CD] and the role of the immune cell compartment remains to be elucidated. Thus, we compared the immune cell compartment of CD fistula to inflammatory CD colitis using imaging mass cytometry [IMC] and immunofluorescence. Methods: A 36-marker panel including structural, functional, and lineage markers for use in IMC was established. This panel was applied to analyse paraffin-embedded CD fistula tract [n = 11], CD colitis [n = 10], and colon samples from non-inflamed controls [n = 12]. Computational methods for cell segmentation, dimensionality reduction, and cell type clustering were used to define cell populations for cell frequency, marker distribution, and spatial neighbourhood analysis. Multiplex immunofluorescence was used for higher resolution spatial analysis. Results: Analysis of cell frequencies in CD fistulas compared to CD colitis and control colonic samples revealed a significant increase in neutrophils, effector cytotoxic T cells, and inflammatory macrophages in CD fistula samples, whereas regulatory T cells were decreased. Neutrophils in CD fistula expressed significantly more matrix metalloproteinase 9 [MMP9], correlating with extracellular matrix remodelling. Neighbourhood analysis revealed a strong association between MMP9+ neutrophils and effector cytotoxic T cells in both CD fistulas and colitis. Conclusions: This study presents the first highly multiplexed single cell analysis of the immune cell compartment of CD fistulas and their spatial context. It links immune cell dynamics, particularly MMP9+ neutrophils, to extracellular matrix remodelling in CD fistulas, offering insights into the complex network of cellular interactions and potential therapeutic targets for CD complications.
CRIS-Team Scopus Importer:2024-09-13
Keywords: fistula; imaging mass cytometry; Penetrating Crohn's disease

The Bisphosphonate Pamidronate is an Intestinal Antiinflammatory Agent in Rat and Mouse Experimental Colitis - Lopez Posadas, Rocío; Mascaraque, Cristina; Gonzalez, Raquel; Suarez, Maria D.; Zarzuelo, Antonio; Martinez-Augustin, Olga; Sanchez De Medina, Fermin (Inflammatory Bowel Diseases, 2016)
Statins have antiinflammatory effects at the cardiovascular level because of inhibition of prenylation, which also probably underlies their therapeutic effects in preclinical models of inflammatory bowel disease. Another inhibitor of prenylation, namely alendronate, reduces colitis in rodents. In this study, we aim to explore the therapeutic potential of second-generation, nitrogen-containing bisphosphonates in 3 preclinical models of colitis.The trinitrobenzenesulfonic acid and dextran sulfate sodium models of rat colitis and the adoptive lymphocyte transfer model of colitis in mice were used. Pamidronate, alendronate, and ibandronate were tested. Treatments were administered in equimolar doses through the oral or intraperitoneal route. The effect of pamidronate on prenylation and cytokine release was assessed in vivo and in vitro.Pretreatment with pamidronate, but not with ibandronate or alendronate, improves chemically induced trinitrobenzenesulfonic acid and dextran sulfate sodium colitis in rats. Moreover, this beneficial effect is extended to lymphocyte transfer colitis. Pamidronate has no effect on intestinal epithelial cells in vitro in terms of cytokine/chemokine release, but enhances IFN-?, IL-6, and IL-10 production by T cells in coculture. Pamidronate also exerts a direct immunomodulatory effect on T cells, favoring Th1 differentiation and impairing Th17 polarization.Pamidronate presents antiinflammatory and immunomodulatory properties in 3 different models of experimental colitis in rodents. This effect requires oral administration and may involve T cells in the gut mucosa, although the exact mechanism is unclear.
EVALuna2:2212

The epithelium takes the stage in asthma and inflammatory bowel diseases - Lopez Posadas, Rocío; Bagley, Dustin C.; Pardo-Pastor, Carlos; Ortiz-Zapater, Elena (Frontiers in Cell and Developmental Biology, 2024)
The epithelium is a dynamic barrier and the damage to this epithelial layer governs a variety of complex mechanisms involving not only epithelial cells but all resident tissue constituents, including immune and stroma cells. Traditionally, diseases characterized by a damaged epithelium have been considered “immunological diseases,” and research efforts aimed at preventing and treating these diseases have primarily focused on immuno-centric therapeutic strategies, that often fail to halt or reverse the natural progression of the disease. In this review, we intend to focus on specific mechanisms driven by the epithelium that ensure barrier function. We will bring asthma and Inflammatory Bowel Diseases into the spotlight, as we believe that these two diseases serve as pertinent examples of epithelium derived pathologies. Finally, we will argue how targeting the epithelium is emerging as a novel therapeutic strategy that holds promise for addressing these chronic diseases.
CRIS-Team Scopus Importer:2024-03-29
Keywords: asthma; barrier; epithelium; IBD; mucus; therapeutics

The pseudokinase MLKL mediates programmed hepatocellular necrosis independently of RIPK3 during hepatitis - Lopez Posadas, Rocío; Becker, Christoph; Günther, Claudia; Tenzer, Stefan; Amann, Kerstin Ute; Billmeier, Ulrike; Atreya, Raja; Fiorino, Gionata; Vetrano, Stefania; Danese, Silvio; Ekici, Arif Bülent; Wirtz, Stefan; et al. (Journal of Clinical Investigation, 2016)
Although necrosis and necroinflammation are central features of many liver diseases, the role of programmed necrosis in the context of inflammation-dependent hepatocellular death remains to be fully determined. Here, we have demonstrated that the pseudokinase mixed lineage kinase domain-like protein (MLKL), which plays a key role in the execution of receptor-interacting protein (RIP) kinase-dependent necroptosis, is upregulated and activated in human autoimmune hepatitis and in a murine model of inflammation-dependent hepatitis. Using genetic and pharmacologic approaches, we determined that hepatocellular necrosis in experimental hepatitis is driven by an MLKL-dependent pathway that occurs independently of RIPK3. Moreover, we have provided evidence that the cytotoxic activity of the proinflammatory cytokine IFN-? in hepatic inflammation is strongly connected to induction of MLKL expression via activation of the transcription factor STAT1. In summary, our results reveal a pathway for MLKL-dependent programmed necrosis that is executed in the absence of RIPK3 and potentially drives the pathogenesis of severe liver diseases.
EVALuna2:2178

The α4β1 Homing Pathway Is Essential for Ileal Homing of Crohn's Disease Effector T Cells In Vivo - Zundler, Sebastian; Fischer, Anika; Schillinger, Daniela; Binder, Marie-Theres; Atreya, Raja; Rath, Timo; Lopez Posadas, Rocío; Voskens, Caroline J.; Watson, Alastair; Atreya, Imke; Neufert, Clemens; Neurath, Markus (Inflammatory Bowel Diseases, 2017)
BACKGROUND: The precise mechanisms controlling homing of T effector (Teff) cells to the inflamed gut in Crohn's disease (CD) are still unclear, and clinical outcome data from patients with inflammatory bowel disease treated with the anti-α4β7 integrin antibody vedolizumab suggest differences between ulcerative colitis and CD. METHODS: Expression of homing molecules was studied with flow cytometry and immunohistochemistry. Their functional role was investigated in in vitro adhesion assays and in a humanized mouse model of T cell homing to the inflamed gut in vivo. RESULTS: Despite in vitro blockade of CD Teff adhesion to mucosal vascular addressin cell adhesion molecule-1 (MadCAM-1) and in contrast to previous observations in ulcerative colitis, anti-α4β7 treatment did not result in reduced Teff cell homing to the colon in vivo. However, the integrin α4β1 was expressed in higher levels on Teffs from patients with CD compared with controls, while its expression in the peripheral blood declined, and its expression in the intestine increased during the course of clinical vedolizumab treatment. Consistently, adhesion of CD Teffs to vascular cell adhesion molecule-1 (VCAM-1) was blocked by inhibition of α4 and α4β1 in vitro. Moreover, in vivo homing of CD Teffs to the ileum was reduced by inhibition of α4 and α4β1 integrins, but not α4β7 integrins. CONCLUSIONS: Our findings suggest that Teff cell homing to the ileum through the axis α4β1-VCAM-1 is an essential and nonredundant pathway in CD in vivo, possibly affecting efficacy of clinical treatment with antiadhesion compounds.
EVALuna2:33825